Laparoscopic fluorescence diagnosis for intraabdominal fluorescence targeting of peritoneal carcinosis: experimental studies - Gahlen, Johannes; Proßt, Rüdiger Lothar; Pietschmann, Matthias Frank; Haase, Thomas; Rheinwald, Markus; Skopp, Gisela; Stern, Josef; Herfarth, Christian (Annals of surgery, 2002)
To assess 5-aminolevulinic acid (ALA)-induced protoporphyrin IX accumulation and fluorescence in peritoneal colon carcinoma metastases and its benefits for laparoscopic fluorescence diagnosis.
Gesehen am 30.03.2021